Effect of climate on asphalt pavement performance using two mechanistic-empirical methods. Issue 5 (16th April 2022) - Ktari, Rahma; Saint-Laurent, Denis; Hornych, Pierre; Hammoum, Ferhat; Marsac, Paul; Nguyen, Mai Lan
ABSTRACT: The objective of this study is to assess the impact of climate on the performance of bituminous pavements with two different methods, and then to examine their impact on actual design scenarios. Three climate cases were selected for the comparisons involving the effect of temperature: one in France (Bordeaux) and two in the United States (Seattle and Phoenix). The case of an experimental site in Québec was also used for comparisons concerning consideration for seasonal variations in ground bearing capacity. The analyses were based on French (Alizé-LCPC) and US (AASHTOWare Pavement ME Design) mechanistic-empirical pavement design approaches. Interesting features of the two design methods are outlined and their fatigue cracking models are linked together. The results of the study highlight the importance, for design purposes, of the empirical fatigue equations as a function of temperature. For the site studied in France, the design results in terms of AC base layer thicknesses indicate that both methods show a similar trend with an increase in temperature. For the site in Québec, which is submitted to severe freeze/thaw cycles, the results show that taking temperature and moisture into account for unbound materials leads to a prediction of more severe permanent deformation. Highlights Presentation of two mechanistic-empirical (ME) methods for pavement design Description of the fatigue equations governing asphalt mixes for design purposes Identification of the parameters used in the design of pavement structures Study of the influence of the climate in France and Québec on pavement performance Comparison of the French and US methods for pavement design and correspondence between them